IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH SCIENTIFIC LEARNING MODEL ON THE THEME OF INDAHNYA KEBERSAMAAN AT GRADE 4 SD ASSISI MEDAN - Marsina Sihotang; Dewi Anzelina; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to improve students’ learning outcomes through Scientific learning model on the theme of “Indahnya Kebersamaan” at Grade 4 SD Assisi Medan for the academic year 2020/2021. This research was Classroom Action Research conducted in two cycles. The subjects in this research were 26 students of grade 4 consisting of 12 male students and 14 female students. Data were collected through observations, tests, and documentations. The learning model applied in this research was Scientific learning model. This research found an increase on students’ learning outcomes on the theme of “Indahnya Kebersamaan” at Grade 4 SD Assisi Medan. This was observed from the results of the initial test in which 8 students reached the target score (30,76%) while 18 students did not reach the target score (69,23%). The average score of the students’ learning outcomes was 68,92. Then, the result of post test in Cycle I revealed an increase on the students’ learning outcomes. It was found that 18 students completed the target score (69,23%) and only 8 students didn’t complete the target score (30,76%). The average score in Cycle I was 76,80. Moreover, the result of post test in Cycle II also showed an increase. Based on the result, 24 students reached the target score (92,30%) while only 2 students did not past the test (7,69%). The average score in this cycle was 86,53. In addition, the results of observations about teachers’ activities in the classroom obtained a value of 96% (very high quality) in Cycle I and 98% (very high quality) in Cycle II. Meanwhile, the results of observations about students’ activities obtained a value of 94 (very good) in Cycle I and 98 (excellent) in Cycle II. Thus, implementing Scientific learning model increased the students’ learning outcomes.